Albumin-bilirubin, Child-Pugh, and model for end-stage liver disease scores for the assessment of prognosis in cirrhotic patients - Zhu, Jia; Guo, Xiaozhong; Qi, Xingshun (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Zhu J, Guo X, Qi X. Albumin-bilirubin, Child-Pugh, and model for end-stage liver disease scores for the assessment of prognosis in cirrhotic patients. Turk J Gastroenterol 2017.